Recent progress in integrated electro-optic frequency comb generation. (April 2021) - Sun, Hao; Khalil, Mostafa; Wang, Zifei; Chen, Lawrence R.
Abstract: Optical frequency combs have emerged as an important tool enabling diverse applications from test-and-measurement, including spectroscopy, metrology, precision distance measurement, sensing, as well as optical and microwave waveform synthesis, signal processing, and communications. Several techniques exist to generate optical frequency combs, such as mode-locked lasers, Kerr micro-resonators, and electro-optic modulation. Important characteristics of optical frequency combs include the number of comb lines, their spacing, spectral shape and/or flatness, and intensity noise. While mode-locked lasers and Kerr micro-resonators can be used to obtain a large number of comb lines compared to electro-optic modulation, the latter provides increased flexibility in tuning the comb spacing. For some applications in optical communications and microwave photonics, a high degree of integration may be more desirable over a very large number of comb lines. In this paper, we review recent progress on integrated electro-optic frequency comb generators, including those based on indium phosphide, lithium niobate, and silicon photonics.